Coping Strategies of Stress Adopted by Female Employees with Children in the University of Cape Coast: Implications for Management Practices - Maison, Regina Sally; Yeboah, Grace; Mensah, Grace Aba; Anane, Mabel (International Journal of Educational Studies, 2019)
The study investigated the coping strategies of stress adopted by female employees with children in the university of Cape Coast. A descriptive study was the designed employed in carrying out the study. Two hundred and four (204) respondents were sampled from 431 female employees with children to answer a set of questionnaires. The results revealed that demands from husbands and thinking of promotional issues were some of the stressors that confronted the respondents. The major effects of stress among the respondents were their inability to plan well and lack of concentration on household chores. The result showed that the most prevailing coping strategy adopted by the respondents was engaging in conversation with friends and family members as well as getting assistance from colleagues. It was concluded that female employees with children in the University of Cape Coast go through stress, which emanates from different sources. Some of the recommendations were that management of the University must educate their employees on and appropriate strategies to cope with their stress. That could be done by management through seminars conferences, workshops on coping strategies of stress.